Penyelesaian Sengketa Hadhanah karena Istri Murtad Menurut Wahbah Al-Zuhaili dan Relevansinya dengan Hukum Islam di Indonesia - Adi Karma; Mahsyar Mahsyar; Misbahuddin Misbahuddin (Program Studi Hukum Keluarga dan Hukum Ekonomi Syariah, Program Pascasarjana Institut Agama Islam Negeri (IAIN) Ternate, 2022)
In Islam, marriage between a Muslim man and a non-Muslim woman is absolutely prohibited. If in a marriage there is a divorce because the wife is out of her religious belief (apostasy), then there is a dispute over the authority of whether the wife can carry out maintenance in the form of care for her child or not. The majority of mazhab scholars allow infidel wives to perform hadhanah on the grounds that mothers have more love for their children. However, Wahbah Az-Zuhaili in his book Fiqhul Islami wa adillatuhu, argues that the right to hadhanah is not stipulated for an apostate wife. Based on the explanation above, the main problem raised in this thesis is how the concept of hadhanah according to Wahbah Az-Zuhaili, what are the source and methodology of his thinking about hadhanah rights because the wife is an apostate and how is it relevant to Islamic law in Indonesia.